The Roles of A Farmer Group in the Development of Organic Rice (BRITANIC) in Krisik Gandusari Village - Ike Wika Santi; Ary Bakhtiar; Yohana Agustina (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2022)
This research aims to investigate the roles of the Nuju Makmur V farmer group in Krisik Gandusari village, Blitar, and to figure out the regeneration of the farmer group in developing organic rice (BRITANIC). The researchers used descriptive analysis and the Likert scale to explore the roles of the farmer group. Moreover, the researchers conducted observation and interviews to investigate the group's regeneration in developing BRITANIC organic rice. The sampling was conducted using the saturated sampling technique in which all 20 members of the farmer group involved in the rice business became the respondents. The results show that the roles of the farmer group, such as conducting regular meetings, establishing cooperation, and managing production units, are categorized as high, with a range value between 34.1 to 42 reaching 100%. The regeneration analysis results show that in the business development of BRITANIC organic rice, the number of Nuju Makmur V farmer group members has decreased from 40 to 20 due to senescence, resettlement, and deaths from Covid-19. In conclusion, the regeneration of young farmers is crucial in developing the high-quality product of BRITANIC rice in Krisik Gandusari Village, Blitar